The Management of the Water as an Effort to Realize a Green Campus in Universitas Sebelas Maret Surakarta - Wiwoho, Jamal; Suryanto, Suryanto; Murtanti, Murtanti; Nugraha, Setya (Universitas Diponegoro, 2021)
The main campus of UNS Surakarta, occupies an area of ± 59,211 Ha. At present, the problem faced by UNS is the increasing of narrow green space, so that it increases rain water and lead to runoff. This process has an impact on the increase in flood discharge and the reduction in the supply of rainwater which becomes ground water reserves. In order to realize a Green Campus that supports sustainable development, efforts have been made relating to groundwater and surface water management. A total of 117 infiltration wells and more than 500 biopori infiltration units have been built, which serve to increase shallow groundwater reserves so that it increases rainwater harvesting and soil moisture. Rainwater that cannot be accommodated in infiltration wells is channeled to the lake named Danau UNS which has an area of 1,206 Ha with a maximum water volume of ± 7,959 m3 , so that it is expected to be able to maintain the shallow ground water balance at the Kentingan UNS Campus. In the future planning, Universitas Sebelas Maret will improve domestic wastewater treatment for other uses, so that there is an efficient use of sustainable clean water